Reliability of 3‐dimensional surface imaging of the face using a whole‐body surface scanner. (3rd November 2021) - Xu, Ya; Frank, Konstantin; Kohler, Lukas; Ehrl, Denis; Alfertshofer, Michael; Giunta, Riccardo Enzo; Moellhoff, Nicholas; Cotofana, Sebastian; Koban, Konstantin Christoph
Abstract: Objective: To the knowledge of the authors, no data about the reproducibility and accuracy of 3‐dimensional surface imaging of the face using a whole‐body scanner are available. Thus, the objective of this investigation was to assess the reproducibility of facial scans acquired using a whole‐body imaging device. Material and Methods: This investigation investigated 220 3‐D scans of a total of 22 healthy volunteers (with a mean age of 29.36 years). Two consecutive 3‐D images using a Vectra WB360 of the volunteers were obtained utilizing a whole‐body imaging device. Predefined distances in the face were performed in each scan and compared. Furthermore, surface deviation between two consecutively captured scans was assessed. Results: The distance with the smallest statistical significance was found to be at the nose with p = 0.998, while the biggest statistical significance was found in the midface with p = 0.658. The area with the biggest surface deviation between the superimposed scans was the neck with a root mean square (RMS) of 1.62 ± 1.71, and the area with the smallest surface deviation was the forehead with a RMS of 0.17 ± 0.05. Conclusion: The whole‐body imaging device investigated in this study can be utilized to capture the face and provides enough accuracy to compare scans. Even though not directly investigated, it can be hypothesized that the error caused by repositioning the patient between a baseline and a follow‐up scan will not be too big to consider measurements performed with the whole‐body imaging device as impractical.